THE EFFECT OF ORGANIZATIONAL CULTURE, WORK-LIFE BALANCE, AND EMPLOYEE INNOVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE SURVEY OF COFFEE SHOP EMPLOYEES IN PALEMBANG CITY - Muhammad Fazal Rizvi; Maftukhatusolikhah; Chandra Zaky Maulana (CV. Cendikiawan Muda Sriwijaya, 2025)
This study aims to analyze the effects of organizational culture, work-life balance, and employee innovation on job performance, with job satisfaction as the intervening variable, among coffee shop employees in Palembang City. This study addresses the significant role of human resources in the service industry, particularly in the growing and competitive coffee shop sector. This study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 180 respondents and analyzed using structural equation modeling (SEM) based on partial least squares (PLS). The results showed that: (1) Organizational culture positively and significantly affects job satisfaction and employee performance, (2) Work-life balance positively and significantly affects job satisfaction and employee performance, (3) Employee innovation positively and significantly affects job satisfaction and employee performance, and (4) Job satisfaction mediates the effects of organizational culture, work-life balance, and employee innovation on employee performance. These findings suggest that improving employee performance can be achieved by creating a supportive work environment, balancing work and personal life, and encouraging innovation, all of which contribute to job satisfaction.